ANALYSIS OF TEACHING METHODS IN AN ENGLISH AS A FOREIGN LANGUAGE (EFL) CONTEXT: A CASE STUDY AT CITRA BERKAT SCHOOL - NI’MAH, MAHSYUROTUN (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: teaching methods, Citra Berkat School, English as Foreign Language(EFL). Nowadays English is an International language which been used as a means of communication in several bilingual schools in Indonesia such as Citra Berkat School. Teaching English as a foreign language is not as easy as teaching the first and second language because the students have not accustomed to acquiring the foreign language. It needs several teaching methods to help the learners successful to use it at school. This research is intended to analyze the teaching methods which are used in Citra Berkat School and the effectiveness of the teaching methods at the school as an EFL (English as Foreign Language) context.This study used qualitative methods by conducting an observation. The subject of this research was an English teacher at Citra Berkat School. The data were taken from the observation result of the ways of the teacher taught in several classes. The sample of the research was chosen purposively.The writer finally finds that there are two kinds of teaching methods which are used in Citra Berkat School, they are Suggestopedia and Communicative Language Teaching. It is shown by several indicators of those teaching method principles which have been applied in that school. Furthermore, eight from nine criteria of effective teaching which are proposed by Jun Li have been applied. Only one of those criteria which has not been applied that is Build Reading Comprehension Ability. It means that the teaching methods used in Citra Berkat School has been effective because 90% of the principles have been completed.It is suggested that the next researcher analyzes the comparison of several teachers who have different characteristics with similar theories. Since the teacher is the role model of the students in the class, the teacher is supposed to improve his/her ability in English.